Plantar calcaneal spurs in older people: longitudinal traction or vertical compression? - Landorf Karl B; Zammit Gerard V; Menz Hylton B; Munteanu Shannon E (Journal of Foot and Ankle Research, 2008)
Abstract Background Plantar calcaneal spurs are common, however their pathophysiology is poorly understood. This study aimed to evaluate the prevalence and correlates of plantar calcaneal spurs in a large sample of older people. Methods Weightbearing lateral foot radiographs of 216 people (140 women and 76 men) aged 62 to 94 years (mean age 75.9, <smcaps>SD</smcaps> 6.6) were examined for plantar calcaneal and Achilles tendon spurs. Associations between the presence of spurs and sex, body mass index, radiographic measures of foot posture, self-reported co-morbidities and current or previous heel pain were then explored. Results Of the 216 participants, 119 (55%) had at least one plantar calcaneal spur and 103 (48%) had at least one Achilles tendon spur. Those with plantar calcaneal spurs were more likely to have Achilles tendon spurs (odds ratio [OR] = 2.0, 95% confidence interval [CI] 1.2 to 3.5). Prevalence of spurs did not differ according to sex. Participants with plantar calcaneal spurs were more likely to be obese (OR = 7.9, 95% CI 3.6 to 17.0), report osteoarthritis (OR = 2.6, 95% CI 1.6 to 4.8) and have current or previous heel pain (OR = 4.6, 95% CI 2.3 to 9.4). No relationship was found between the presence of calcaneal spurs and radiographic measures of foot posture. Conclusion Calcaneal spurs are common in older men and women and are related to obesity, osteoarthritis and current or previous heel pain, but are unrelated to radiographic measurements of foot posture. These findings support the theory that plantar calcaneal spurs may be an adaptive response to vertical compression of the heel rather than longitudinal traction at the calcaneal enthesis.